HUBUNGAN ANTARA KOORDINASI MATA DAN KAKI DENGAN AKURASI PASSING PADA PEMAIN SEPAKBOLA U-12 SSB JTS KOTA JAMBI - Adi Nur Putra, Eka Yoga; Boy Indrayana; Fitri Khairunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was based on the low passing ability of players, which was presumed to be related to visual-motor coordination. The purpose of this study was to examine the relationship between eye-foot coordination and passing accuracy. This study applied a quantitative approach with a correlational design. All 20 players were selected as the sample using a total sampling technique. The study was conducted at Persijam Stadium, Jambi City, from February 3 to February 17, 2026. Data were collected using the Soccer Wall Volley Test and the Loughborough Soccer Passing Test. Both instruments were used to measure eye-foot coordination and passing accuracy. Data analysis included normality testing, linearity testing, and Pearson correlation testing. The results of the analysis showed that the data were normally distributed and met the assumption of linearity. The correlation test produced an r-value of -0.716 with a significance value of 0.000 < 0.05. These results indicated a significant relationship with a strong correlation level and a negative direction. The better the coordination, the lower the error score, resulting in improved passing accuracy. Based on these findings, it can be concluded that eye-foot coordination has a significant relationship with the improvement of passing accuracy in 12-year-old soccer players. Therefore, training programs focused on developing visual-motor coordination should be systematically designed to optimize the development of players’ basic technical skills.